Haplotype phase inference - Donnelly, Peter (Henry Stewart Talks, 2004)
The problem of haplotype phase prediction and inference of frequencies, Computational methods: parsimony and Clark's algorithm, Computational methods: maximum likelihood and the EM algorithm, Computational methods: Bayesian approaches, The advantages of a Coalescent-based prior, Coping with large numbers of markers, Review of available software
Archived at 2021/02/25